THEORETICAL FOUNDATIONS OF CORPORATE GOVERNANCE (European Journal of Economics, Finance and Business Development, 2026)
The article examines the theoretical and practical aspects of corporate governance as one of the key concepts in the modern global economy. The economic essence, objectives, and functions of corporate governance in the context of globalization and the development of corporate structures are analyzed. Special attention is given to major corporate governance theories, including agency theory, stakeholder theory, transaction cost theory, resource dependence theory, and political theory. The paper also discusses conflicts of interest between shareholders and managers and highlights the role of corporate governance in increasing investment attractiveness and improving corporate performance.